PEREMPUAN DAN PENDIDIKAN ISLAM RAMAH LINGKUNGAN: PERAN KOLABORATIF ANTARA PKK DAN TA’MIR MASJID DALAM MENGATASI SAMPAH LIMBAH RUMAH TANGGA - Mutholingah, Siti; Amrullah, Zen (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
Household waste specifically for women and children in the form of sanitary napkins and diapers is still a major problem in environmental cleanliness. This is becauseSia of some people who believe that sanitary napkin and diaper waste should not be burned. Ta'mir of the mosque as a religious figure and Family Empowerment and Welfare as social figures have a very important role in this problem around the mosque. The aims of this research are: 1) to analyze the role of ta'mir and PKK in dealing with napkins and baby diaper waste in the environment around the Baitul Ghoni Mosque, and 2) to analyze the types of activities carried out by the ta'mir and PKK in overcoming waste of sanitary napkins and baby diapers in the environment. This research uses a case study. Data collection was carried out through interviews and observation. There are 2 findings from this research. First, the role of the ta'mir of the mosque is as an Islamic educator who provides religious insight regarding environmental cleanliness and health from the perspective of Islamic law and the role of PKK as activators activities regarding the handling of sanitary napkin and baby diaper waste. Second, the form of activities carried out by the mosque ta'mir in collaboration with PKK in dealing with sanitary napkin and diaper waste, namely holding Islamic studies on purity and risalatul mahidh, holding health seminars on the use of cloth napkins and cloth diapers as an alternative to replace sanitary napkins and disposable diapers, giving fines for throwing away sanitary napkins and diapers in the river for residents around the Baitul Ghoni mosque